Nomadic State: Speciﬁ cs and Nature of Functioning of Institutes of the Power (Journal of Philosophy Culture and Political Science, 2019)
Speciﬁ cs and character of functioning of authority institutions of nomadic state connected with its typological features; low evolution potential, low sustainability, narrow real functions. In this context, as author thinks, patronymia becomes dominating form of regulating of social and other relations in nomadic society. It is based on genealogic, kinship relations and patriarchal relations within the family.